Selection of ornamental peppers elite lines for ethylene-insensitive - Ramalho do Rêgo, Elizanilda; de Souza Souto Freitas, Nardiele; dos Santos Pessoa, Angela Maria; Duarte Silva, Priscila; Finger, Fernando Luiz; Monteiro do Rêgo, Maílson (Revista Ceres, 2022)
Peppers belongs to Capsicum genus and have a lot of different varieties. They can be different uses such as potted ornamental plants. Retail market for this type of pepper requires the development of a greater number of commercial cultivars with adequate ornamental characteristics as well as an extended shelf life (post-production). Ethylene exposure causes adverse effects in ornamental pepper post-production. Then, the goal of this study was to select ornamental pepper elite lines (Capsicum annuum L.) for ethylene-insensitive. The experiment was conducted at the Laboratory of Plant Biotechnology of the Center for Agricultural Sciences of the Federal University of Paraíba, Areia, PB. The experiment was arranged in a completely randomized design. Eight elite lineages and two control cultivars evaluated at three times 48, 72 and 96 hours after ethylene exposure were disposed in a split-plot arrangement. Each treatment was composed of ten repetitions. The data were submmited to analysis of variance, Scott-Knott criteria (5%), and regression analysis. The leaves demonstrated to be more sensitive to ethylene while fruits were more insensitive. It is recommended selection of UFPB lines: 56.8.24.1; 56.26.15.1 and 56.26.34.1 to participate in trials tests aiming at registration of new ethylene-insensitive cultivars.